Use of Redox Probes for Characterization of Layer-by-Layer Gold Nanoparticle-Modified Screen-Printed Carbon Electrodes. Issue 2 (1st January 2017) - Bishop, Gregory W.; Ahiadu, Ben K.; Smith, Jordan L.; Patterson, Jeremy D.
Abstract : The electrochemical characteristics of bare and surface-modified screen-printed carbon electrodes (SPCEs) were compared using voltammetric responses of common redox probes to determine the potential role of nanomaterials in previously documented signal enhancement. SPCEs modified with gold nanoparticles (AuNPs) by layer-by-layer (LbL) electrostatic adsorption were previously reported to exhibit an increase in voltammetric signal for Fe(CN)6 3−/4− that corresponds to an improvement of 102% in electroactive surface area over bare SPCEs. AuNP-modified SPCEs prepared by the same LbL strategy using the polycation poly(diallyldimethylammonium chloride) (PDDA) here were found to provide no beneficial increase in electroactive surface area over bare SPCEs. Though similar improvement in voltammetric signal of Fe(CN)6 3−/4− was found for AuNP/PDDA-modified compared to bare SPCEs in these studies, results with other redox couples ferrocene methanol (FcMeOH/FcMeOH + ) and Ru(NH3 )6 3+/2+ indicated no difference between the electroactive surface areas of modified and bare SPCEs. Furthermore, gold present on AuNP/PDDA-modified SPCEs accounted for only 62 (±12)% of the electroactive surface area. The previously reported improvement in electroactive surface area that was attributed to the inclusion of AuNPs on the SPCE surface appears to have resulted from a misinterpretation of the non-ideal behavior of Fe(CN)6 3− as a redox probe for bare SPCEs.